2021
DOI: 10.1246/bcsj.20200364
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Addition of Acetal-Derived Benzyl Radicals Generated from Low-Valent Titanium-Mediated C–O Bond Cleavage

Abstract: A new method for the generation of benzyl radicals from acetals via low-valent titanium-mediated homolytic C–O bond cleavage is presented. The low cost and availability of the developed titanium reagent enable efficient access to α-alkoxy carbon radical species via the developed reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In the subsequent rate-determining stage, the CÀ O bond is directly cleaved, and an alkyl radical is formed without the participation of the CÀ Cl species; subsequently, it reacts with alkenes. In addition to the metalation-protonation pathway as reported in our previous study, [18] the low-valent Ti-promoted HAT from DMA was unexpectedly found to be another route for terminating the radical process, although its proportion would be largely dependent on the alkenes used.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…In the subsequent rate-determining stage, the CÀ O bond is directly cleaved, and an alkyl radical is formed without the participation of the CÀ Cl species; subsequently, it reacts with alkenes. In addition to the metalation-protonation pathway as reported in our previous study, [18] the low-valent Ti-promoted HAT from DMA was unexpectedly found to be another route for terminating the radical process, although its proportion would be largely dependent on the alkenes used.…”
Section: Methodssupporting
confidence: 57%
“…Representative cyclopentadienyl (Cp)‐based Ti reagents Cp 2 TiCl 2 and Cp*TiCl 3 demonstrated only slight reactivity to the C−O cleavage (entries 2 and 3). TiCl 4 (collidine) [10] and TiCl 4 (tmeda), [18] which were previously reported by our group, were not very effective (entries 4 and 5). Mn powder as a reductant was less suitable than Zn (entry 6).…”
Section: Resultsmentioning
confidence: 64%
“…The same strategy was also applied to the generation of α-alkoxy carbon radicals from benzyl acetals. 16 The radical was subsequently intercepted by acrylonitrile.…”
Section: Scheme 4 Ti-mediated Alcohol C-o Radical Homolysismentioning
confidence: 99%
“…For instance, Suga, Ukaji, and Shu et al developed a direct homolytic cleavage of alcoholic CÀ O bonds under low-valent titanium catalysis. [40][41][42][43][44] Additionally, the oxidative addition modes (metal insertion or nucleophilic attack), catalyzed by transition metals such as Ni, Re, Pd, Au, and Ir, have been applied to the CÀ OH bond cleavage of alcohols, possibly with a subsequent coupling step. Moreover, the CÀ OH bond cleavage via β-OH elimination has been reported in the transition metal Mo/Ru catalyzed reaction systems (Figure 2b).…”
Section: Introductionmentioning
confidence: 99%